Remaining Useful Life Assessment of Pipeline via Finite Element Analysis and FITNET FFS Method by Evaluating Burst Pressure of Cylindrical Pipeline and Probabilistic Method - Abdullah, Ahmad Zaimmul Adli (IRC, 2021)
Corrosion is one of the major causes of pipeline system hazard. The corrosion affects the burst pressure of the cylindrical pipeline and over time, the probability of failure gradually increases.